(untitled) (Journal of Asian Geography, 2025)
Climate change has emerged as a critical issue that demands the attention of global communities, becoming a primary concern for many nations. Sri Lanka's Central Province is particularly vulnerable to these shifts. This study aims to outline the expected patterns of temperature and rainfall in the Central Province under different climatic scenarios, using various models across diverse socio-economic pathways. The data for this analysis were obtained from the global coordination system established by the Coupled Model Intercomparison Project Phase 6. Utilizing carbon emission scenarios SSP2-4.5 and SSP5-8.5, a range of models were examined, and overarching conclusions were drawn using MiniTab 17 software. Under the SSP2-4.5 scenario, the consolidated results from the various models suggest that the average projected temperature for the Central Province from 2020 to 2100 will rise by 1.17°C, with May identified as the warmest month, experiencing a temperature increase of 1.33°C. Average rainfall is expected to increase by 105.56 mm, with November showing the most significant rise at 124.62 mm. In the context of the SSP5-8.5 scenario, the combined results indicate that the average temperature is projected to rise by 1.94°C during the same period, with May again exhibiting the highest temperature increase at 2.17°C. Average rainfall is expected to increase by 125.01 mm, with November encountering the greatest uplift at 184.77 mm. By understanding the projected temperature and rainfall changes in the Central Province, sustainable development in the region can be strengthened, thereby contributing to Sri Lanka's broader economic advancement.